2010
DOI: 10.1038/nature09606
|View full text |Cite
|
Sign up to set email alerts
|

Sugar transporters for intercellular exchange and nutrition of pathogens

Abstract: Sugar efflux transporters are essential for the maintenance of animal blood glucose levels, plant nectar production, and plant seed and pollen development. Despite broad biological importance, the identity of sugar efflux transporters has remained elusive. Using optical glucose sensors, we identified a new class of sugar transporters, named SWEETs, and show that at least six out of seventeen Arabidopsis, two out of over twenty rice and two out of seven homologues in Caenorhabditis elegans, and the single copy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

52
1,653
6
18

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 1,301 publications
(1,729 citation statements)
references
References 57 publications
52
1,653
6
18
Order By: Relevance
“…Several nodulin genes are also activated in response to inoculation with AM fungi (Harrison 1998 The other nodulin gene that was up-regulated significantly in the basal part of mycorrhizal protocorms containing the fungal pelotons was SvNod9, which codes for a putative bidirectional sugar transporter of the SWEET family. These are uniporters (Chen et al 2010) that can transfer hexoses across the plasma membrane in both directions, depending on the sugar gradient. SWEETs can serve for sugar export from cells, and they can be exploited by bacterial and fungal pathogens to acquire carbohydrates for energy and carbon (Chen et al 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several nodulin genes are also activated in response to inoculation with AM fungi (Harrison 1998 The other nodulin gene that was up-regulated significantly in the basal part of mycorrhizal protocorms containing the fungal pelotons was SvNod9, which codes for a putative bidirectional sugar transporter of the SWEET family. These are uniporters (Chen et al 2010) that can transfer hexoses across the plasma membrane in both directions, depending on the sugar gradient. SWEETs can serve for sugar export from cells, and they can be exploited by bacterial and fungal pathogens to acquire carbohydrates for energy and carbon (Chen et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…These are uniporters (Chen et al 2010) that can transfer hexoses across the plasma membrane in both directions, depending on the sugar gradient. SWEETs can serve for sugar export from cells, and they can be exploited by bacterial and fungal pathogens to acquire carbohydrates for energy and carbon (Chen et al 2010). The nodule-specific MtN3 is a member of the M. truncatula SWEET family, and an involvement in bacteroid nutrition inside the nodule has been suggested (Bapaume and Reinhardt 2012), even though previous studies indicated that dicarboxylic acids are likely the carbon source supplied to intracellular bacteroids (see in White et al 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The source is involved in the storage and transport of nutrients in plants (Ruan 2014;Rolland et al 2002). However, sugar cannot be transported independently across the plant cell membrane system and requires the assistance of appropriate sugar transporters, such as MSTs (monosaccharide transporters) (Slewinski 2011), SUTs (sucrose transporters) (Kuhn and Grof 2010;Ayre 2011) and SWEETs (sugars will eventually be exported transporters) (Chen et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…SWEET shows the function of bidirectional reversible transport of sugar, and promotes the diffusion of sucrose to the apoplast pathway through transmembrane across the gradient of concentration on cell efflux (Baker et al 2012;Lin et al 2014;Eom et al 2015). Since SWEET was first discovered using Forster resonance energy transfer (FRET) by optical glucose sensors (Chen et al 2010), SWEET family members have been identified by genome-wide analyses in different plant species, such as Arabidopsis (Chen et al 2010), rice (Yuan and Wang 2013), tomato (Feng et al 2015), soybean (Patil et al 2015) and cucumber (Hu et al 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation